Finance-security: Where to go? - Nina Boy (Finance and Society, 2017)
This forum contribution addresses the state of the art in the finance-security literature, identifying problems with the "financialisation of security" and "securitisation of finance" analytics, as well as a tendency to treat "money" as a non-financial object in ways that fail to recognise money's own (financial) parameters of safety and security. In response, it calls for greater engagement with political and financial security, instead of merely (political) securitisation and financialisation.
Keywords: 300